Atmospheric Hygroscopic Ionogels with Dynamically Stable Cooling Interfaces Enable a Durable Thermoelectric Performance Enhancement. Issue 49 (13th October 2021) - Ni, Feng; Xiao, Peng; Zhang, Chang; Zhou, Wei; Liu, Depeng; Kuo, Shiao‐Wei; Chen, Tao
Abstract: In thermoelectric generator (TEG) systems, heat dissipation from their cold sides is an accessible, low‐cost, and effective way to increase the temperature gap for their thermoelectric performance enhancement. Although significant efforts have been dedicated mediated by hygroscopic hydrogel coolers as self‐sustained alternatives for effective heat removal, it still remains a challenge for overcoming instabilities in their cooling process. The inevitable mechanical deformation of these conventional hydrogels induced by excessive water desorption may cause a detached cooling interface with the targeted substrates, leading to undesirable cooling failure. Herein, a self‐sustained and durable evaporative cooling approach for TEG enabled by atmospheric hygroscopic ionogels (RIGs) with stable interfaces to efficiently improve its thermoelectric performance is proposed. Owing to its superior hygroscopicity, the RIGs can achieve higher heat dissipation for TEG through water evaporation than that of common commercial metal heat sinks. Moreover, its favorable adhesion enables the RIG closely interact with the TEG surface either in static or dynamic conditions for a durable thermoelectric performance enhancement. It is believed that such a self‐sustained evaporative cooling strategy based on the RIG will have great implications for the enhancement of TEG's efficiency, demonstrating a great promise in intermittent thermal‐energy utilizations. Abstract : A hygroscopic ionogel (RIG) is developed to dissipate waste heat from working thermoelectric generators (TEGs) through self‐sustained evaporative cooling to efficiently enhance their electric output. Moreover, the well‐designed adhesive property of the RIG ensures a stable cooling interface with the targeted TEGs surface either in static or dynamic conditions for a durable improvement of thermoelectric performance.